GLOBAL ANTI-TERRORIST NETWORKING (Annual of the Faculty of Philosophy in Skopje, 2013)
The technologies of the information age in particular help network forms of organizations whose members/groups are geographically detached or carryout different but complementary actions.In this paper emphasis is put on the shift from hierarchical to networked organizational forms which will be different specifically gradual and uneven, although the results of the research confirm the evolution of terrorism to “network warfare ” and creating a “new" terrorism. Consequently anti-terrorism activities need to be adapted to the field of organization, strategy and technology.
Keywords: GLOBAL TERRORISM; ANTI-TERRORISM; NETWORKING; INTELLIGENCE INFORMATION